Multidimensional Analysis of Changing Eating Habits: Understanding the Coffee Shop Phenomenon in Indonesia - Safitri, Rahmauldianti; Ramadani, Elvy; Oceani, Fakhiratunnisa Putri; Tanziha, Ikeu (Universitas Airlangga, 2025)
Globalization and technological development have led to changes in lifestyles, including eating habits such as coffee consumption. The proliferation of cafes is evidence that coffee consumption has become a trend among adolescents and young adults who are exhibiting shift toward unhealthy eating patterns, such as consuming of high-sugar coffee. This study aims to analyse changes in eating habits in adults based on the theory of A Multidimensional Approach to the Study of Food Habits. This study used a systematic review using PRISMA method. Articles were sourced from two databases, Scopus and Google Scholar covering the past 8 years (2016-2024) with a total of 18 articles reviewed. The results showed that culture, ideology, food consumption, and preferences significantly influence coffee consumption habits. In Indonesia coffee culture not only about taste, but also involves social interaction, self-identity, and self-expression. Additionally, it was influenced by access, habits, needs, psychological factors, culture, and health. Coffee selection preferences were shaped by technological and socioeconomic factors including (promotions, discounts, employment, and income). This study provides insights into the factors influencing changes in eating habits, particularly coffee consumption, and can inform the development of effective interventions to promote healthy eating habits in this age group.